2008
DOI: 10.1002/cne.21650
|View full text |Cite
|
Sign up to set email alerts
|

Sall3 is required for the terminal maturation of olfactory glomerular interneurons

Abstract: Sall3 is a zinc finger containing putative transcription factor and a member of the Sall gene family. Members of the Sall gene family are highly expressed during development. Sall3-deficient mice die in the perinatal period because of dehydration and display alterations in palate formation and cranial nerve formation (Parrish et al. [2004] Mol Cell Biol 24:7102-7112). We examined the role of Sall3 in the development of the olfactory system. We determined that Sall3 is expressed by cells in the olfactory epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 115 publications
(207 reference statements)
3
21
1
Order By: Relevance
“…Indirect immunoblot analysis of proteins obtained from rat PC-12 pheochromocytoma cells recognizes a single band of $60kDa corresponding to rat TH (manufacturer's specifications). Staining in the rat brain with this TH antibody corresponds to previous studies reporting TH staining in different parts of rat brain (Harrison et al, 2008). Immunofluorescent staining of sections throughout the medulla oblongata of rats produced a pattern of TH immunoreactivity identical to previous descriptions (Armstrong et al, 1982).…”
Section: Antibody Characterization and Titrationsupporting
confidence: 68%
“…Indirect immunoblot analysis of proteins obtained from rat PC-12 pheochromocytoma cells recognizes a single band of $60kDa corresponding to rat TH (manufacturer's specifications). Staining in the rat brain with this TH antibody corresponds to previous studies reporting TH staining in different parts of rat brain (Harrison et al, 2008). Immunofluorescent staining of sections throughout the medulla oblongata of rats produced a pattern of TH immunoreactivity identical to previous descriptions (Armstrong et al, 1982).…”
Section: Antibody Characterization and Titrationsupporting
confidence: 68%
“…In Sall3-null mice, a complete absence of TH expression is observed in the OB. But in the ventral midbrain, the expression of TH remains (Harrison et al 2008). Interestingly, in Nurr1-deficient mice, TH expression is absent from the substantial nigra and nigrostriatal pathway but is maintained in the OB (Le et al 1999).…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies showed that the Sall3-deficient animals exhibited a complete absence of TH + cells in the OBs throughout development (Harrison et al 2008). This phenotype may be caused by a regulation function of Sall3 on TH gene expression.…”
Section: Sall3 and Th Co-express In The Mouse Obsmentioning
confidence: 97%
See 1 more Smart Citation
“…Several transcription factors have been implicated in the specification of the different neuronal populations. The zinc finger transcription factor sp8, for instance, appears to be involved in the generation of interneurons expressing calretinin (8), and analysis of Sall3 mutant mice (9) points to a role of this factor in the dopaminergic, tyrosine hydroxylase-positive lineage (10). Furthermore, it appears that interneuron diversity relies on the combinatorial expression of such transcription factors.…”
mentioning
confidence: 99%